2021
DOI: 10.1108/jfep-07-2020-0152
|View full text |Cite
|
Sign up to set email alerts
|

Did Brexit change asset co-movements?

Abstract: Purpose This paper aims to examine the impact of the Brexit referendum on the risk structure of financial asset prices. Co-movements are analysed using daily price returns of major stock and bond indices as well as commodities and exchange rates from June 2014 to June 2018. The authors used a multivariate GARCH model to study the dynamics of the conditional correlation matrix of asset returns. It was found that the conditional variances and correlations of assets spike on and after the Brexit referendum and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…This information is crucial for Islamic asset managers and mutual funds to predict the further shocks that might happen during the process of exit from the EU and take necessary measures by hedging their funds against risks. A recent study of Saha et al (2021) found that Brexit has a significant effect on financial asset co-movements, which indicates the importance of including the Brexit effect in financial decision-making.…”
Section: Multivariate Generalised Autoregressive Conditional Heteroskedastic-dynamic Conditional Correlationsmentioning
confidence: 99%
“…This information is crucial for Islamic asset managers and mutual funds to predict the further shocks that might happen during the process of exit from the EU and take necessary measures by hedging their funds against risks. A recent study of Saha et al (2021) found that Brexit has a significant effect on financial asset co-movements, which indicates the importance of including the Brexit effect in financial decision-making.…”
Section: Multivariate Generalised Autoregressive Conditional Heteroskedastic-dynamic Conditional Correlationsmentioning
confidence: 99%